Komunikasi Digital dan Perubahan Sosial Masyarakat Pedesaan - Mashis, Batinuha Musyahadah; Aksa, Ahmad Habiburrahman; Muayyanah, Asyrotul; Satriya, M Khasya (Prodi KPI FDPM IPMAFA Bekerjasama dengan Mafa Press IPMAFA Pati, 2023)
The digital era has brought significant changes in the lives of rural communities, including in Sukolilo Pati village. This research uses a qualitative descriptive method to describe the current phenomenon. The article outlines the challenges and opportunities faced by village communities in the face of digital technology development. Limited internet access, the potential for economic empowerment, improved access to information and education, and the role of technology in health and public services are the main focus of the discussion. In addition, this article examines the impact of social and cultural changes that occur due to the development of digital technology, including adjustments to social norms and traditional attitudes in rural communities. With this understanding, the importance of technological accessibility and efforts to equalize internet access in villages, as well as the social changes therein, become important topics of discussion to ensure that the full benefits and vigilance of the digital era can be felt by all rural communities.